ANALISIS FAKTOR YANG MEMPENGARUHI KUNJUNGAN ANTENATAL CARE (ANC) - Tanjung, Faisah; Effendy, Ismail; Utami, Tri Niswati; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (Jurnal Kebidanan Khatulistiwa, 2024)
Background: Based on WHO data (2020), Indonesia's Antenatal Care (ANC) coverage percentage (82%) is still far from the standards set compared to other countries, where pregnancy checks for ANC (K1) coverage are 96.1%, and ANC (K4) coverage is 96.1%. amounting to 74.1%. The target of the strategic plan (Renstra) related to K1 is 100& and K6 coverage of pregnant women is 78%, in general it has not reached the target. The aim: of the research is to determine the analysis of factors influencing Antenatal Care (ANC) visits in the Sambas Port Health Center Working Area, Sibolga City in 2022 Metodh: The design of this research is analytical research using retrospective. The population in the study was all postpartum mothers ≤2 months, namely 216 people in October 2023. The sample used the Slovin formula, namely 68 respondents. The data used uses primary and secondary data. Data analysis using univariate, bivariate and multivariate using binary regression tests. Resulth: The research results were obtained using the chi square test, there was an influence of knowledge with Antenatal Care (ANC) visits (p= 0.017), there was no influence of employment with Antenatal Care (ANC) visits (p= 0.514), there was an influence of the role of health workers with Antenatal visits Care (ANC) (p= 0.001), there is an influence of husband's support with Antenatal Care (ANC) visits (p= 0.004), There is an influence of the attitude of health workers with Antenatal Care (ANC) visits (p= 0.027) and there is no influence of health facilities with Antenatal Care (ANC) visits (p= 0.017). The most dominant factor is the role of health workers with Antenatal Care (ANC) visits (p= 0.002) with an OR value of 6.160 (2.018-18.807). Conclusion:  the is that there is an influence of knowledge, attitude, role of health workers, husband's support, attitude of health workers with Antenatal visits in the Sambas Port Health Center Working Area. It is hoped that health workers at the Sambas Harbor Health Center will improve the quality of KIA services so that they can increase KIA patient satisfaction.